Association between Insulin Resistance and Benign Prostatic Hyperplasia - Sarkar, Susmita; Saha, Atanu; Dawn, Indranil (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction:Benign prostatic hyperplasia (BPH) is the most common benign disease in older men characterized by stromal and epithelial cell hyperplasia. Insulin is an independent risk factor and a promoter of BPH. Insulin resistance may change the risk of BPH through several biological pathways. Aim and objective: Aim of our studyis to estimate the insulin resistance and prostatic specific antigen level in the patients suffering from benign prostatic hyperplasia and compare them with the control. Materials and Methods : Hospital based cross sectional case control study.40 BPH-patients (aged above 50 years), clinically diagnosed and supported by serum PSA and USG findings were selected as case. Results:Insulin resistance was found to be elevated in the patients suffering from BPH. HOMA-IR score of cases was compared with the controls and found to be significantly elevated.A significant increase in fasting glucose level and PSA level were found in cases compared to controls. Conclusion: The insulin resistance was found to be significantly higher in patients.Further study regarding the relationships between metabolic syndrome and benign prostate diseases, including its underlying mechanisms is necessary. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 240-245